Perianal Fixed Drug Eruption Mimicking Herpes Infection Due to Ibuprofen- A Rare Case Report - Taruna Singh, Rahul Kumar Sharma, (International Journal of Innovative Research in Medical Science, 2017)
The fixed drug eruption (FDE) is a special form of drug induced dermatological disorder characterized by development of erythematous or pigmented patches. We are presenting a very rare case of FDE mimicking perianal herpes. A 45 years old man presented with herpetiform perianal ulcers with history of multiple episodes of similar painful perianal ulceration for the last 3 years. There was no history of exposure to multiple sexual partners. The Tzanck’s smear and herpes serology was negative. There was a temporal relationship between Ibuprofen intake and development of lesions. The oral provocation test was in favour of FDE secondary to Ibuprofen. There are very few case reports of herpetiform FDE. So far in our knowledge this is the first case report of FDE mimicking the perianal herpes from India. So FDE should be considered in the cases of treatment nonresponsive herpes lesions.